Improvement of the LTE handover algorithms in terms of quality of service - Samia Hakkou; Tomader Mazri; Nabil Hmina (Institute of Advanced Engineering and Science, 2022)
With the emergence of new possibilities and user requirements in the field of mobile technology, long term evolution (LTE) is the most popular as it offers high-speed service. LTE is a 4G wireless network developed by the 3rd generation partnership project (3GPP). The implementation of LTE is strongly affected by the quality of service (QoS) when transfer management is the main issue. Handover management allows communication to be maintained when switching from one base station to another. In this paper, we explain that there are several types of transfers that are not efficient in terms of quality of services such as throughput, signal-to-interference-plus-noise ratio (SINR), and latency. For this purpose, we thought of creating a new algorithm on the A1 and A3 events and the reference signal received quality (RSRQ). Our algorithm is effective compared to other already available algorithms using the NS3 network simulator.